An Overview ForWiMAX NetworksCovering Some Handover Algorithms - Huda H. Saheb, Bashar J. Hamza, Ahmed Fahem AL-Baghdadi, WasanKadhim Saad, Saif H. Abdulwahed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As a consequence of Needs to continue in terms of data rates, speed and quality of service, various aspects of wireless networks are evolving. In the same network or across different technology and service provider networks, those aspects must be adaptable. Worldwide interoperability for microwave Access (WiMAX) is also one of the networks of the future century (4G) That requires additional research. However, the handoff structure that concerns the transition of mobile stations within the scope of network from one base station to another similar homogeneous network (horizontal handover) or various heterogeneous network (vertical handover) is a major consideration for WiMAX to achieve mobility. In the current context, this article discusses the characteristics of WiMAX, Concentrate on possible handoff-related study problems, generally addressing the two forms of handover. this essay concentratemore On homogeneous performance of handover . In WiMAX, mobility aspects are defined as an individual layer of the Mobility Agent (MA), above its MAC layer, and some indication of a network layer.